Optical coherence tomography angiography at the acute phase of optic disc edema - Marie-Bénédicte Rougier; Mélanie Le Goff; Jean-François Korobelnik (Eye and Vision, 2018)
Abstract Background The differential diagnosis of optic disc edema at the acute phase can be challenging. OCT angiography (OCTA) is a new technology allowing the visualization of the peripapillary vascular network and optic disc capillaries. The peripapillary network alterations of glaucoma and chronic non-arteritic anterior ischemic optic neuropathy (NAION) were reported. However, no OCTA studies on acute optic disc edema from various causes. The aim of this project was to use OCTA to demonstrate the vascular changes the optic nerve head of various types of optic disc edema at the acute phase. Methods In this retrospective study, patients with non-arteritic anterior ischemic optic neuropathy (NAION), papillitis or papilledema were recruited. Each patient was imaged using the AngioPlex™ CIRRUS™ HD-OCT device(model 5000, Carl Zeiss Meditec, Inc., Dublin, USA) with a scanning area of 6 × 6 mm2 centered on the optic disc. A morphological analysis of the peripapillary network was performed. For some patients with unilateral optic disc edema, a quantitative analysis was performed using a swept-source OCT-A system (PLEX® Elite 9000, Carl Zeiss Meditec, Inc., Dublin, USA). Vessel perfusion density and flux index of the peripapillary area were calculated. Results Eight eyes with NAION (4 patients), 12 eyes with papillitis (6 patients) and 25 eyes with papilledema (13 patients) were imaged. The apparent disappearance or moderate pattern alteration of the peripapillary capillary vessels were observed in patients with NAION or papillitis, respectively. For papilledema, the capillaries at the surface of the optic disc were dilated and tortuous, but no peripapillary network pattern changes were observed. The quantitative analysis did not show any difference of peripapillary network between NAION and healthy eyes. For papillitis, the flux index was higher in inflammatory eyes compared to the healthy eyes in average (p = 0.03). Conclusion At the acute phase, the morphological analysis of OCT-A appeared to be more useful than the quantification analysis, facilitating the differentiation between the three kinds of ONH edema: ischemic, inflammatory and papilledema.